INDEPENDENCE OF JUDGES IN THE IMPLEMENTATION POWERS OF JUSTICE - Nurul Qamar (Faculty of Law, Universitas Jenderal Soedirman, 2015)
This article aims to explore the independence of the judiciary as an important pillar of a rule of law. Independence of the judiciary is a necessary condition for maintaining the rule of law, only constitutional law has legitimacy that must be upheld and the court should have the ability to perform a task in deciding the law. The independence of judges to examine, prosecute and deciding have guaranteed in the Constitution of the Republic of Indonesia Year 1945 and Act No. 48 of 2009 on Judicial Power, with the purpose judge in his judicial function can actually examine, prosecute and deciding on cases based on the law and justice.Keywords : Judge, Judicial Independence, Judiciary Power.